1993
DOI: 10.1161/01.hyp.22.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular reactivity to stress predicts future blood pressure status.

Abstract: Cardiovascular reactivity to stress may have a pathophysiological role in neurogenic hypertension. We studied the value of measuring blood pressure change during standardized mental and physical challenges to prediction of resting blood pressure status 6.5 years later among 206 middle-aged adults and their 164 children, with the latter group originally being tested while enrolled in elementary through high school. After adjustment for age, resting blood pressure, and body mass index at study entry, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
201
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(221 citation statements)
references
References 17 publications
17
201
0
3
Order By: Relevance
“…Our findings are supported, however, by observations that earlier gestational age also within its normal variation is associated with adverse cardiovascular health outcomes such as the resting BP level in adult women 2 and mortality from cerebrovascular disease. 37 Together with previously described associations of BP reactivity with both resting BP level 38 and magnetic resonance imaging-diagnosed subclinical cerebral infarctions and related findings, 39 our findings suggest that these associations of pre-and perinatal conditions with adult disease are probably in part explained by associations with BP reactivity. In men, we found that lower gestational age was related to lower BP and TPR reactivity.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings are supported, however, by observations that earlier gestational age also within its normal variation is associated with adverse cardiovascular health outcomes such as the resting BP level in adult women 2 and mortality from cerebrovascular disease. 37 Together with previously described associations of BP reactivity with both resting BP level 38 and magnetic resonance imaging-diagnosed subclinical cerebral infarctions and related findings, 39 our findings suggest that these associations of pre-and perinatal conditions with adult disease are probably in part explained by associations with BP reactivity. In men, we found that lower gestational age was related to lower BP and TPR reactivity.…”
Section: Discussionsupporting
confidence: 85%
“…[2][3][4][5][6][7][8][9] This supports the reactivity hypothesis, which states that exaggerated physical or psychological responses to stress identify subgroups with increased cardiovascular risk. 10 However, there are some controversies regarding whether this represents a casual relationship.…”
supporting
confidence: 71%
“…Most of them have observed a relation between an exaggerated response of BP to mental stress tasks and subsequent BP status after a few years of follow-up. [12][13][14][15][16][17][18][19] An important study published by Carroll et al, 20 found that the response of BP to mental stress task Figure 3 Changes of BP during mental arithmetic task in subjects who developed SH or who did not.…”
Section: Discussionmentioning
confidence: 99%
“…11 A relation between an exaggerated response of BP to mental stress tasks and subsequent BP status has been observed in some prospective studies. [12][13][14][15][16][17][18][19] However, other prospective studies did not find these results: a recent published study has shown that pressure reactions to stress provide only a minimal independent contribution of BP at follow-up. 20 The objective of this study was to assess the independent contribution of BP response to mental stress tasks in the development of sustained hypertension (SH) in untreated mildly hypertensive subjects, after 5 years of follow-up.…”
Section: Introductionmentioning
confidence: 92%